From verbal to adjectival - Geda Paulsen; Maria Tuulik; Ahti Lohk; Ene Vainik (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave)
This study addresses categorization issues related to adjective candidates in Estonian, focusing on the category of participles. The aim of the analysis was to assess the ranges of the prototypical adjective and to determine its degree of deviation on the prototypicality scale. The investigation was based on a group of validated adjectives – selected adjectives included in the Basic Estonian Dictionary – and two control groups of more and less lexicalized participles. We tested seven morphosyntactic corpus patterns characteristic of adjectives. The test patterns were based on the prototypical features of the adjective, as well as on observations made in the actual lexicographic analysis. To assess the sample words and determine the significance of the test patterns from the point of view of defining adjectivity, we used deviation analysis. The results of this study can be applied to establish a measure of adjectivity for lexicographic judgments when distinguishing, for instance, lexicalized participles from regular ones.